The Dilemmas and Improvement Paths of Civil Protection of Personal Information in the Context of Data and Platform Compliance - Lei, Yimin (International Journal of Social Sciences and Public Administration, 2026)
From the perspective of data compliance and platform governance, this paper adopts empirical research and normative analysis to conduct a systematic study on the civil protection of personal information in China. An examination of current institutional practices reveals prominent dilemmas in key areas such as legislative coordination, judicial application, platform liability enforcement, and individual rights remedies. These dilemmas mainly include insufficient adaptability of legal rules, unbalanced allocation of the burden of proof, ineffective implementation of platform compliance, and high costs for individual rights relief. Based on China’s existing legal framework and judicial practice, this paper proposes a systematic improvement path for the civil protection of personal information from five aspects: refining legislation, unifying adjudication standards, improving platform internal control mechanisms, optimizing remedy channels, and establishing a multi-stakeholder collaborative regulatory system. This can provide practical reference for the protection of personal information civil rights and the standardized operation of platforms. This article only focuses on the analysis of civil remedies and does not delve into the mechanism of civil execution connection. The empirical materials mainly consist of public judgments made by some courts, which restricts the research scope to a certain extent. In the future, we can combine new application scenarios such as algorithm recommendation and cross-border data transmission to further improve the rules for civil compensation and liability determination, promote the collaborative efforts of multiple governance mechanisms, and achieve a dynamic balance between personal information protection and platform compliance in the context of sustainable development of the digital economy.